Development of android-based edutainment game to improve mathematics problem-solving ability - Yulia Romadiastri; Mujiasih Mujiasih; Riska Ayu Ardani; Mohd Afifi Bahurudin Setambah (Journal of Educational and Learning Studies, 2025)
The development of technology has presented several choices of unique, creative, and innovative learning media that can be used in the learning process. Besides being a challenge, involving innovative and creative learning media also provides opportunities for students to improve their mathematical problem-solving skills. This research will focus on research on the development of edutainment game media that can be used on smartphones (Android). Media development is carried out by adapting the ADDIE model which contains five (5) stages, namely analysis, design, development, implementation, and evaluation. Furthermore, descriptive quantitative analysis was conducted to review the feasibility of the media. The results of the analysis show that edutainment games are feasible as learning media to improve mathematical problem-solving abilities in terms of validity, practicality, and effectiveness.